2023
DOI: 10.56553/popets-2023-0028
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Concerns and Acceptance Factors of OSINT for Cybersecurity: A Representative Survey

Abstract: The use of Open Source Intelligence (OSINT) to monitor and detect cybersecurity threats is gaining popularity among Cybersecurity Emergency or Incident Response Teams (CERTs/CSIRTs). They increasingly use semi-automated OSINT approaches when monitoring cyber threats for public infrastructure services and incident response. Most of the systems use publicly available data, often focusing on social media due to timely data for situational assessment. As indirect and affected stakeholders, the acceptance of OSINT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Surveillance can be defined as the systematic monitoring of individuals or groups for a given purpose [32,52]. In the case of OSINT for cybersecurity, there are two kinds of systems: Cyber Threat Intelligence (CTI), which focuses on the detection and analysis of cyber threats, and risk mitigation systems, which work towards identifying actors and groups [46].…”
Section: Acceptance Of Surveillance Technologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Surveillance can be defined as the systematic monitoring of individuals or groups for a given purpose [32,52]. In the case of OSINT for cybersecurity, there are two kinds of systems: Cyber Threat Intelligence (CTI), which focuses on the detection and analysis of cyber threats, and risk mitigation systems, which work towards identifying actors and groups [46].…”
Section: Acceptance Of Surveillance Technologiesmentioning
confidence: 99%
“…Looking at the OSINT systems which were developed for cybersecurity purposes in a systematic study, Riebe et al [46] identified 73 systems, from which 11 discussed ELSI implications. Especially when systems aim at focusing on particular actors, this could include the profiling of individuals [14].…”
Section: Privacy Impact Of Osintmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many ethical considerations related to cybersecurity and data privacy. For example, there may be ethical concerns around the collection and use of personal data, the use of surveillance technologies, and the potential for discrimination or bias in algorithms and decision-making processes [7]- [9]. It is important to consider these ethical implications when designing policies and technologies related to cybersecurity and data privacy.…”
Section: Introductionmentioning
confidence: 99%